WHY RELIGION MATTERS AND THE PURPOSES OF HIGHER EDUCATION: A DIALOGUE WITH HUSTON SMITH. Issue 1 (March 2015) - Kenney, Garrett
Abstract This article examines Huston Smith's critique of and remedy for modernity from the perspective of a college professor who adopted "Why Religion Matters" (2001) as required reading for undergraduates. Smith's heartfelt plea to consider, if not embrace, the common wisdom of traditional religious worldviews deserves a hearing. But Smith's approach is also in need of qualification, supplementation, and critique. This article, ironically, finds the needed qualification, supplementation, and critique in Huston Smith's much earlier publication, The Purposes of Higher Education (1955). This article provides the dialogue.